Healthy Sports and the Importance of Oxygen Balance in Maintaining Physical, Spiritual and Social Health Towards Complete Prosperity - M.Mat , Siti Hadiaty Yuningsih, S.Si.,; Chayandri, Rini; Vaidyanatahan, Sundarapandian (International Journal of Health, Medicine, and Sports, 2024)
This text raises the importance of maintaining and improving health as a form of gratitude for the health blessings bestowed by God. The main focus is on the role of Health Sports in maintaining physical, spiritual and social health. It was explained that Health Sports not only strengthens body functions, but also stimulates holistic growth and development of individuals towards complete prosperity, in accordance with the definition of the World Health Organization (WHO). It is important to understand that Health Sports is not just heavy physical activity, but also includes activities that are relaxed and without emotional burden. The main goal is to increase the level of dynamic health, enabling individuals to be able to live their daily lives independently, without relying on the help of others. Additionally, the text discusses the vital role of oxygen in the functioning of the human body. Oxygen is an important element in the formation of energy, water vapor and carbon dioxide. Sufficient oxygen levels affect the health of the circulatory system, brain and all body organs. It is emphasized that understanding the oxygen balance in the body is key to maintaining health and preventing disease.